EFFECTIVENESS OF MATHEMATICS LEARNING USING PROBING MODEL - PROMPTING LEARNING ON STUDENT ABILITY ABOUT CRITICAL VIII STUDY ABOUT CLASS VIII SMP N 1 SEDAYU BANTUL DISTRICT - Diah Pramusinta; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The research is conducted because the learning process only centered by the teacher so that the student’s ability is still not enough. The research aims to know the differences in the student’s ability for critical thinking. The learning process use probing – prompting learning model and live learning model then compare the effectiveness both of the model towards the student’s ability of critical thinking. The population of this research is VIII B, VIII D, and VIII F SMP N 1 Sedayu because the classes have the same ability. The sample was taken by a random sampling technique then VIII B was selected as the experiment class and VIII D as a control class. The design of the research is a posttest only control design. The technique of resource data use test. The instrument of resource data is problem description (posttest). The instrument test of resource data use validity test and reliability test. The technique of data analysis is a normal test, homogeny test, then hypothesis test with the first hypothesis test and second hypothesis test. The result of the hypothesis test with significant level 5% and dk = 60 show that : (1) , so there are differences in the student’s ability of critical thinking that use probing – prompting learning model and live learning model. (2)  dan  sehingga , so the student’s ability of critical thinking that uses probing – prompting learning model is more effective then use a live learning model.